ANALISIS DESKRIPTIF TERAPEUTIK KOMUNITI BAGI PECANDU NARKOBA DI YAYASAN SEKAR MAWAR - Sukmana Ajang Jakaria; Yumna Yumna; Asrul Al Umari; Vira Fahrisa Salsabila (UIN Sunan Kalijaga Yogyakarta, 2021)
Therapy is one of the ways or methods of healing that is carried out by a person who experiences physical or psychological disorders or symptoms. The birth of therapy was initially pioneered by Islamic religious leaders, namely the Prophet Muhammad which at that time was only more about the concept of doctrine. Along with the development of time and era, western experts in the field of psychology examined more deeply about the therapy, which was doctrinaire, became a new scientific discipline later. In writing this article, the author also describes the rehabilitation process provided by the Sekar Mawar Foundation in Bandung City to drug addicts. By using two approaches through CBT-based therapy and also counselling with community therapeutic techniques, it is hoped that drug addicts will be able to recover aspects of their lives, whether physical, psychological, social and spiritual.